Relationship Between Strategic Direction, Core Competencies And Firm Competitiveness Among Manufacturing Firms In Uganda - Oguta, James; Kimwolo, Andrew; Cheruiyot, Thomas (SEISENSE (PRIVATE) LIMITED, 2022)
Purpose- The paper examines the relationship between strategic direction, core competencies, and firm competitiveness among manufacturing firms in Uganda. Design/Methodology- This study collected quantitative data from 410 manufacturing firms using self-administered questionnaires, while qualitative data was collected from 10 manufacturing firms using an interview guide. Quantitative data were augmented by qualitative methods, allowing us to comprehend the phenomenon under study completely. To study the nature of reality, an explanatory cross-sectional survey was employed. While the content analysis was used to investigate qualitative data, regression analysis was used to evaluate hypotheses. Findings- According to the research, a firm's competitiveness improves when its executives concentrate on their capabilities. The findings validated the theoretical foundations of the resource-based viewpoint. Practical Implications- As a result of the findings, manufacturing firms may increase strategic leadership's influence on competitiveness by ensuring that workers have proper directions and that the core competencies are identified and leveraged to ensure efficiency and effectiveness in operations. The findings may assist CEOs and policymakers design strategies and policies to increase the level of competitiveness of their firms.